Bridging calculus and engineering practice: an instructional video series by UiTM Cawangan Pulau Pinang educators - Libasin, Zuraira; Azudin, Ahmad Rashidi; Mazeni, Noor Azizah; Idris, Nur Azimah; Samsudin, Norshuhada (2025)
Calculus is a core subject in engineering education, yet many students find it abstract and struggle to connect its concepts with practical engineering applications. This perceived disconnect often leads to low engagement, surface-level understanding, and difficulty in applying mathematical knowledge in realworld engineering contexts. To address this issue, we have developed Bridging Calculus and Engineering Practice, an instructional video series designed to contextualize fundamental calculus concepts through practical engineering applications. The series consists of three short episodes, each highlighting a specific calculus topic and its relevance in engineering, such as rate of change in thermodynamics, definite integrals in salt mixing in Continuous Stirred Tank Reactor (CSTR), and optimization I engineering design. Each video combines clear conceptual explanations, real-world scenarios, and animated visuals using digital tools such as Canva. This approach enhances student engagement, supports independent learning, and promotes deeper understanding by making learning more relevant and application focused. This initiative aligns with the SUSED2025 theme of Transforming Education, Driving Innovation, and Advancing Lifelong Learning for an Empowered World by leveraging digital media to enhance mathematics education and empower engineering students with meaningful, lifelong learning experiences.